Analisis Validitas dan Reliabilitas Instrumen Pengukuran Mengenal Bentuk-Bentuk Geometri - Atik Mufidah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
In conducting research activities, researchers certainly really need valid data. Setting up the device makes maneuvering an important part of the research strategy. Making the instrument serves as a tool in collecting the necessary data. The assessment instrument that will be made in this study is to recognize geometric shapes for children aged 4-5 years. The reason for making instruments to recognize geometric shapes is because there are still many children aged 4-5 years who still do not know them properly. The purpose of making an instrument about recognizing geometric shapes for children aged 4-5 years is to determine the feasibility of the indicators contained in the instrument as a reference in learning about recognizing geometric shapes. The research method used in this research is descriptive quantitative method with survey technique. The research instrument used data collection techniques through questionnaires with 7 teachers of RA Muslimat NU Masyithoh 05 Banyurip Ageng Pekalongan City as instrument assessors. In determining the validity of the instrument using aiken's v and to assess the constancy or reliability of the raters, the researcher used kappa statistics using SPSS-16. The results of this study concluded that the instrument items for recognizing geometric shapes for children aged 4-5 years proved valid, steady and significant.